2023
DOI: 10.3390/cimb45040173
|View full text |Cite
|
Sign up to set email alerts
|

The Use of DArTseq Technology to Identify Markers Related to the Heterosis Effects in Selected Traits in Maize

Abstract: Spectacular scientific advances in the area of molecular biology and the development of modern biotechnological tools have had a significant impact on the development of maize heterosis breeding. One technology based on next-generation sequencing is DArTseq. The plant material used for the research consisted of 13 hybrids resulting from the crossing of inbred maize lines. A two-year field experiment was established at two Polish breeding stations: Smolice and Łagiewniki. Nine quantitative traits were observed:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…Association mapping is also conducted for hybrids of many plant species [94][95][96][97]. Recently, an attempt has been made to study the relationship between molecular markers and heterosis effects in maize [33]. The results show that the integration of molecular genetics with traditional methods of plant selection guarantees an objective assessment of the phenotype taking into account environmental factors and provides the opportunity to eliminate undesirable genotypes at the seedling stage, thus reducing breeding time.…”
Section: Discussionmentioning
confidence: 99%
“…Association mapping is also conducted for hybrids of many plant species [94][95][96][97]. Recently, an attempt has been made to study the relationship between molecular markers and heterosis effects in maize [33]. The results show that the integration of molecular genetics with traditional methods of plant selection guarantees an objective assessment of the phenotype taking into account environmental factors and provides the opportunity to eliminate undesirable genotypes at the seedling stage, thus reducing breeding time.…”
Section: Discussionmentioning
confidence: 99%
“…Bocianowski et al [39] used NGS technology and associative mapping to identify markers related to the heterosis effect in maize. Using the same methods, Sobiech et al [40] identified markers linked to the resistance of maize plants to fusarium. In turn, Tomkowiak et al [41] identified six SNP markers (1818; 14506; 2317; 3233; 11657; 12812) located inside genes, on chromosomes 8, 9, 7, 3, 5 and 1, related to the amount of yield in corn.…”
Section: Discussionmentioning
confidence: 99%